Quality 4.0 in higher education: integrating industry 4.0 technologies in higher education quality management practices - Abnoulgid, Fatima; Aouhassi, Sarah; Mansouri, Khalifa; Akef, Fatiha (Frontiers in Education, 2025)
Quality management practices play a critical role in higher education, ensuring the reliability and efficiency of educational processes. Today, with the advent of the Higher Education 4.0 era, higher education institution leaders are facing increasing challenges, particularly with regard to the need to ensure quality education to a diverse audience, adapt these practices to the challenges posed by digital technologies and new pedagogical requirements, meet labor market demands, and manage limited financial resources. Just as in Industry 4.0, where the integration of digital technologies is transforming production processes, Higher Education 4.0 aims to rethink education through an integrated digital approach. This article investigates the adaptation of quality management practices to Higher Education 4.0. It explores, through a literature analysis, the integration of emerging technologies like online learning platforms, virtual reality, artificial intelligence, and data analysis into educational processes to enhance the quality of teaching and learning. This study aims to highlight the correlation between quality management practices and Higher Education 4.0 technologies (Industry 4.0 outputs), thus providing a practical framework to guide educational institutions in their transition to a more digital and quality-oriented higher education model.